Improving Self-Awareness Through Islamic Education: its Implication on Life Detecting Good Awareness Impacts a Good Lifestyle an Analysis of Literature Study - Jailani, Mohammad Mohammad Jailani; Risma Mega Utami, Risma Mega Utami (UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
Self-awareness is something that distinguishes it from other creatures. In Islamic Education, self-awareness is self-reflection. Awareness can change life into the latest version through the sensitivity of the heart to know the values of events in his life. Every human being has a different level of consciousness. There are still many Muslims who abandon the obligation to worship including a lack of self-awareness of their responsibilities as Muslims or Muslim women. The word awareness looks trivial to some people who do not understand the importance of the awareness that exists within. If you are able to contemplate it, there will be a lot of awareness that comes to mind about what is the purpose of human life in the world. This journal aims to increase the awareness of every Muslim towards a rational (reasonable) life in order to build self-existence and achieve the grace of Allah SWT. So that Islamic education does not only aim to produce knowledgeable human beings, but also faithful and civilized. Islamic education will always influence every individual to make a person who is always aware in the future. The world is the best charity field to achieve happiness in the hereafter, so the level of awareness is very important for it self.